2019
DOI: 10.1101/756064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Refining modules to determine functionally significant clusters in molecular networks

Abstract: Module detection algorithms relying on modularity maximization suffer from an inherent resolution limit that hinders detection of small topological modules, especially in molecular networks where most biological processes are believed to form small and compact communities. We propose a novel modular refinement approach that helps finding functionally significant modules of molecular networks. The module refinement algorithm improves the quality of topological modules in protein-protein interaction networks by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Higher scores indicated that the clusters are more distinct or separated from one another (range 0=clusters completely overlap to 1=no connections between clusters). While modularity captures the extent to which clusters are distinct from one another, it is often unable to detect small clusters (Fortunato and Barthelemy, 2007;Kaalia and Rajapakse, 2019). To investigate the network in more depth, density between clusters was calculated as the sum of existing ties between two clusters divided by total possible number of ties between them (range 0=no connection to 1=complete connection).…”
Section: Network Levelmentioning
confidence: 99%
“…Higher scores indicated that the clusters are more distinct or separated from one another (range 0=clusters completely overlap to 1=no connections between clusters). While modularity captures the extent to which clusters are distinct from one another, it is often unable to detect small clusters (Fortunato and Barthelemy, 2007;Kaalia and Rajapakse, 2019). To investigate the network in more depth, density between clusters was calculated as the sum of existing ties between two clusters divided by total possible number of ties between them (range 0=no connection to 1=complete connection).…”
Section: Network Levelmentioning
confidence: 99%
“…Based GO term-protein annotations, many research have employed information content (IC) of GO terms [22][23][24][25] to compute similarity between two proteins in order to predict PPI. These methods have succeeded in the development of protein-related tasks, including PPI prediction [26][27][28][29][30][31][32][33]. Despite their success, IC-based methods have been unable to fully capture functional properties of proteins and structural properties of PPIN.…”
mentioning
confidence: 99%